Belatacept Does Not Inhibit Follicular T Cell-Dependent B-Cell Differentiation in Kidney Transplantation - de Graav, Gretchen N.; Hesselink, Dennis A.; Dieterich, Marjolein; Kraaijeveld, Rens; Verschoor, Wenda; Roelen, Dave L.; Litjens, Nicolle H. R.; Chong, Anita S.; Weimar, Willem; Baan, Carla C. (Frontiers in Immunology, 2017)
Humoral alloreactivity has been recognized as a common cause of kidney transplant dysfunction. B-cell activation, differentiation, and antibody production are dependent on IL-21+CXCR5+follicular T-helper (Tfh) cells. Here, we studied whether belatacept, an inhibitor of the costimulatory CD28-CD80/86-pathway, interrupts the crosstalk between Tfh- and B-cells more efficiently than the calcineurin inhibitor tacrolimus. The suppressive effects of belatacept and tacrolimus on donor antigen-driven Tfh–B-cell interaction were functionally studied in peripheral blood mononuclear cells from 40 kidney transplant patients randomized to a belatacept- or tacrolimus-based immunosuppressive regimen. No significant differences in uncultured cells or donor antigen-stimulated cells were found between belatacept- and tacrolimus-treated patients in the CXCR5+Tfh cell generation and activation (upregulation of PD-1). Belatacept and tacrolimus in vitro minimally inhibited Tfh-cell generation (by 6–7%) and partially prevented Tfh-cell activation (by 30–50%). The proportion of IL-21+-activated Tfh-cells was partially decreased by in vitro addition of belatacept or tacrolimus (by 60%). Baseline expressions and proportions of activated CD86+ B-cells, plasmablasts, and transitional B-cells after donor antigen stimulation did not differ between belatacept- and tacrolimus-treated patients. Donor antigen-driven CD86 upregulation on memory B-cells was not fully prevented by adding belatacept in vitro ( 35%), even in supratherapeutic doses. In contrast to tacrolimus, belatacept failed to inhibit donor antigen-driven plasmablast formation ( 50% inhibition vs. no inhibition, respectively, p < 0.0001). In summary, donor antigen-driven Tfh-B-cell crosstalk is similar in cells obtained from belatacept- and tacrolimus-treated patients. Belatacept is, however, less potent in vitro than tacrolimus in inhibiting Tfh-cell-dependent plasmablast formation.